An Analytical Study of the Conduct Oneself While Inordain of Phracakkhubalthera - (วังสิงห์), พระเสาร์คำ ธีรธมฺโม; ณ วันนา, ไพรินทร์; -, พระครูสิริปริยัตยานุศาสก์; วิชัย, วิโรจน์ (Ganesha Journal, 2018)
A Critical Study on the Ecclesiastical Life of Cakkhupàla Thera aimed to 1) study the principle of being a monkhood in Buddhism, 2) investigate the biography of Cakkhupàla Thera, and 3) analyze the ecclesiastical life of Cakkhupàla Thera. The results revealed that the principle of being a monkhood in Buddhism involved with the Gantha-dhura or burden of study, Vipassanà-dhura or burden of insight and Pàrisuddhi-sãla or morality consisting in purity. According to Cakkhupàla Thera, he was a Buddhist monk who practiced strictly and was highly persistent. He had practiced solemnly until both eyes blind with attained the Enlightenment as the Sukkhavipassaka or bare-insight worker. He became a disabled person and lived a life of patience, not being burdened by others, living a normal life, being faithful to one another and benefiting both himself and others. After he had attained sainthood, he lived his life as usual such as taught the people and the monks. Regarding his intrinsic characteristic, he was a type of Buddhi-carita or one of intelligent temperament and upheld the four principles of being a monkhood in Buddhism as follows: (1) Ganthadhura: the burden of studying the Scriptures, (2) Vipassanà-dhura: burden of insight development, (3) The perfection of heedfulness, and (4) Pàrisuddhi - sãla: morality consisting in purity. He finally had accomplished the Ultimate Goal in Buddhism –Nibbàna.